Competitiveness of regional healthcare systems in the Republic of Kazakhstan - Agilbaeva, A.A.; Smaylov, B.T.; Vechkinzova, E.A. (BUKETOV BUSINESS REVIEW, 2022)
Object: The purpose of this article is to identify the competitive advantages of the regional socio-economic systems of the regions of the Republic of Kazakhstan, namely the healthcare system since one of the chains of the socio-economic systems of the region is healthcare. Methods: The method of analysis. Results: The visibility of regional indicators is revealed, focusing on the statistical indicators provided by government agencies. The results of research in this direction can be used by national and regional medical doctors, scientists, representatives of health systems, and politicians in the field of public health. Conclusions: Absolute indicators of health care reflect the number of hospital organizations and beds in them for patients, the number of doctors, giving a dynamic picture of the provision of the population with medical care in each of the regions of Kazakhstan. Based on the analysis of the dynamic picture of relative health indicators, the authors formed a competitiveness rating of the regions of the Republic of Kazakhstan. The authors also identified areas for further exploratory research reflecting the development of regional competitiveness.